An Introduction to Annuities - Michael S. Gutter; Lisa Leslie (EDIS)
An annuity contract is purchased from a life insurance company. The individual gives the insurance company a lump-sum payment or a series of payments. In return, the company will provide a stream of payments to the individual. Although an annuity is purchased from a life insurance company, it serves a different purpose than life insurance. Below is a chart comparing life insurance to annuities. This 4-page fact sheet was written by Michael S. Gutter and Lisa Leslie, and published by the UF Department of Family, Youth and Community Sciences, March 2014.